2010
DOI: 10.1016/j.endend.2009.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and its association with carotid intima-media thickness in hypertensive and non hypertensive patients

Abstract: Carotid intima-media thickness (C-IMT) measured noninvasively by ultrasonography is widely used as a marker for increased risk of cardiovascular disease. Also hyperuricemia (HU) is a well recognized risk factor for cardiovascular diseases. The study was designed to assess the relation between hyperuricemia and carotid intima-media thickness C-IMT in patients with and without hypertension (HTN).This study included 126 patients divided into four groups: (1) Group A, included 59 hypertensive patients with hyperur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
3
1
0
Order By: Relevance
“…This study also showed that CIMT was higher in normotensive hyperuricemic controls than among the normotensive non hyperuricemic controls, and that the difference was statistically significant. This was consistent with the results by Elsayed et al [40] and Tavil et al [41]. This means that hyperuricemia could be a risk factor for atherogenesis independent from hypertension.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study also showed that CIMT was higher in normotensive hyperuricemic controls than among the normotensive non hyperuricemic controls, and that the difference was statistically significant. This was consistent with the results by Elsayed et al [40] and Tavil et al [41]. This means that hyperuricemia could be a risk factor for atherogenesis independent from hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…This means hyperuricemia per se could be a risk factor for atherosclerosis in hypertensive patients and by necessary implication an indicator of increased cardiovascular disease. This is consistent with the findings by Elsayed et al [40]. This study also showed that CIMT was higher in normotensive hyperuricemic controls than among the normotensive non hyperuricemic controls, and that the difference was statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…In concordance with "Normative aging study" [25], Elsayed et al [26], Tavil Y et al [2] our study also demonstrated that the hyperuricemia predicts the development of hypertension. So, controls of hyperuricemia can control hypertension in CRF patients and halt or slow the further progression of atherosclerosis.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies had found elevated SUA to be significantly associated with subclinical atherosclerosis among the hypertensive population. Both Tavil et al 22 and Elsayed et al 23 found in their studies that CIMT level was statistically higher among the hypertensive population with elevated SUA when compared with a control group with normal blood pressure and normal SUA. These results were also supported by Mutluay et al 24 whose findings showed that CIMT level was significantly associated with hyperuricemia in hypertensive subjects as compared with hypertensive subjects without elevated SUA, even after controlling for metabolic and clinical factors.…”
Section: Discussionmentioning
confidence: 90%